Analysis of a Functional IL-6 Gene Polymorphism in HLAB27 Associated and Intermediate Uveitis Gives New Insight in Disease Pathogenesis and Commonality with Other Autoimmune Diseases - Lindner Ewald; Langner-Wegscheider Beate; Sarny Stephanie; Renner Wilfried; El-Shabrawi Yosuf (Journal of Immunology Research)
Purpose. Interleukin 6 (IL-6) plays a crucial role in both adaptive and innate immunity. The rs1800795 gene polymorphism of IL-6 is associated with various autoimmune diseases, like multiple sclerosis. Methods. 134 patients with HLAB27 positive iridocyclitis, 84 patients with intermediate uveitis, 132 controls, and 65 HLAB27 positive controls were recruited for the present case-control study. Main outcome measures were genotype distribution and allelic frequencies determined by polymerase chain reaction. Results. The frequency of carriers of the minor allele for rs1800795 was significantly higher in patients with intermediate uveitis compared to controls (p=0.04; OR: 1.46; CI: 1.02–2.11). Frequencies of the minor allele for rs1800795 did not differ significantly in patients with HLAB27 associated uveitis when compared to controls (p>0.05). Conclusion. These findings further deepen our understanding of the commonality between multiple sclerosis and intermediate uveitis. Given the functionality of the investigated polymorphism, new pathophysiological insights are gained that help to evaluate possible therapeutic targets.